2013
DOI: 10.1186/1471-2350-14-57
|View full text |Cite
|
Sign up to set email alerts
|

The carrier rate and mutation spectrum of genes associated with hearing loss in South China hearing female population of childbearing age

Abstract: BackgroundGiven that hearing loss occurs in 1 to 3 of 1,000 live births and approximately 90 to 95 percent of them are born into hearing families, it is of importance and necessity to get better understanding about the carrier rate and mutation spectrum of genes associated with hearing impairment in the general population.Methods7,263 unrelated women of childbearing age with normal hearing and without family history of hearing loss were tested with allele-specific PCR-based universal array. Further genetic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
20
1
2
Order By: Relevance
“…To obtain a more representative estimate of the carrier frequency in the Chinese population, we combined data from two other articles to conduct a meta‐analysis (Table ). Our data show that carrier frequencies of most mutations in different parts of China have some degree of difference, but few showed significant differences (p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To obtain a more representative estimate of the carrier frequency in the Chinese population, we combined data from two other articles to conduct a meta‐analysis (Table ). Our data show that carrier frequencies of most mutations in different parts of China have some degree of difference, but few showed significant differences (p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
“…This study conducted an epidemiological survey of the 15 most frequently reported hearing loss mutations in a Chinese newborn cohort. On comparison with the data for the eight mutants commonly studied, the carrier frequencies were found to be quite similar, 4.26% (our study) vs 4.05% (Guangzhou) without significant difference. The other seven mutations included in our study detected an additional 11.7% subjects carrying pathogenic hearing loss mutations (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…However, in a carrier screening for normal hearing female populations of childbearing age in South China, 9 subjects (in 7,263 women, 0.12%) were found carrying GJB3 c.538C > T in a heterozygous state, suggesting that it might act as an autosomal recessive mutation (Yin et al ., 2013). Moreover, the variant c.538C > T has been recategorized as "benign" lately, based on allele frequency (Shearer et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Yin ve ark.nın doğurganlık çağında, eşiyle akrabalığı olmayan ve işitme kaybı öyküsü bulunmayan 7.263 Çinli kadın üzerinde yaptığı bir çalışmada; işitme kaybı için patojen genetik mutasyon (GJB2 "235 del C %1,76", GJB3, SLC26A4 "919-2A>G %1,24" ve mtDNA 12S rRNA) taşıyıcılığı %4,17 olarak bildirilmiştir. 27 Aynı çalışmada, GJB2 ve SLC26A4 genlerinde farklı heterozigot mutasyon saptanan ailelerden alınan fetal ör-neklemlerde (koryonik villüs, amniyosentez veya fetal kanda); fetal heterozigot mutasyon saptananlarda işitmenin normal, ancak homozigot mutasyon saptananlarda ciddi işitme kaybı görülebileceği vurgulanmaktadır. 27 İşitme kaybıyla karakterize 400'ün üzerinde sendrom tanımlanmakla birlikte; X'e bağlı geçişli Alport sendromu, otozomal resesif geçişli Usher ve Pendred sendromları, otozomal dominant geçişli Waardenburg sendromu ile birlikteliğinin sık olduğu bildirilmektedir.…”
Section: Yenidoğanda İşitme Tarama Programı Ve Yönetimiunclassified
“…27 Aynı çalışmada, GJB2 ve SLC26A4 genlerinde farklı heterozigot mutasyon saptanan ailelerden alınan fetal ör-neklemlerde (koryonik villüs, amniyosentez veya fetal kanda); fetal heterozigot mutasyon saptananlarda işitmenin normal, ancak homozigot mutasyon saptananlarda ciddi işitme kaybı görülebileceği vurgulanmaktadır. 27 İşitme kaybıyla karakterize 400'ün üzerinde sendrom tanımlanmakla birlikte; X'e bağlı geçişli Alport sendromu, otozomal resesif geçişli Usher ve Pendred sendromları, otozomal dominant geçişli Waardenburg sendromu ile birlikteliğinin sık olduğu bildirilmektedir. 28 …”
Section: Yenidoğanda İşitme Tarama Programı Ve Yönetimiunclassified